2017
DOI: 10.4018/978-1-5225-1054-3.ch016
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Optimization of Tourism Networks

Abstract: A tourism network is determined by close collaboration among various stakeholders working interactively on common problems or issues through formal and informal approaches. As many cases highlight, informal relationships contribute to the formation of formal partnerships. In this study a game theoretical model is applied to explain the decisional process of entrepreneurs about forming partnerships in formal tourism networks. The model shows that, in terms of Nash equilibrium, the cooperative optimization of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Model derivation and simulation data analysis showed that most of the tourism enterprises are indeed motivated to engage in green development, and the formation of a green tourism supply chain is a dynamic evolution process (Huang et al, 2019). Asero et al (2017) used the game theory model to explain the decision-making process of entrepreneurs in establishing partnerships in the formal tourism network. The research results show that in the Nash equilibrium model, when entrepreneurs have the same business objectives and common tourism vision, the cooperative optimization of a tourism network can be achieved (Asero et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Model derivation and simulation data analysis showed that most of the tourism enterprises are indeed motivated to engage in green development, and the formation of a green tourism supply chain is a dynamic evolution process (Huang et al, 2019). Asero et al (2017) used the game theory model to explain the decision-making process of entrepreneurs in establishing partnerships in the formal tourism network. The research results show that in the Nash equilibrium model, when entrepreneurs have the same business objectives and common tourism vision, the cooperative optimization of a tourism network can be achieved (Asero et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Asero et al (2017) used the game theory model to explain the decision-making process of entrepreneurs in establishing partnerships in the formal tourism network. The research results show that in the Nash equilibrium model, when entrepreneurs have the same business objectives and common tourism vision, the cooperative optimization of a tourism network can be achieved (Asero et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%